1995
DOI: 10.1203/00006450-199511000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Serine and Glycine Metabolism in Primary Culture of Ovine Fetal Hepatocytes

Abstract: Previous in vivo studies in the ovin e fetus have demonstrat ed net serin e production by the fetal liver, a pattern not seen in the adult sheep. The goal of this study was to determine the major metabolic pathway s responsible for fetal hepatic serine production by using stable isotop e methodology in primary culture of late ges tation ovine fetal hepatocytes. Specificall y selected tracers of glycine were added to individual cultures, with production of labeled serine determin ed after 24 h of incubati on. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In the adult mammalian liver it has been shown that serine is primarily cleaved to methylenetetrahydofolate and glycine, and glycine can then be oxidized to CO 2 (Yoshida & Kikuchi 1972). In addition, it has been shown that there is significant glycine oxidation in the liver of the late gestation fetal sheep, and 14 CO 2 produced by the liver from [ 14 C]glycine can account for at least 70% of the total 14 CO 2 produced by the fetus (Thureen et al 1995). Thus, the infused serine in the current study could have been converted to [ 14 C]glycine, which is a possible candidate for oxidation in the fetal liver during IGF-I infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the adult mammalian liver it has been shown that serine is primarily cleaved to methylenetetrahydofolate and glycine, and glycine can then be oxidized to CO 2 (Yoshida & Kikuchi 1972). In addition, it has been shown that there is significant glycine oxidation in the liver of the late gestation fetal sheep, and 14 CO 2 produced by the liver from [ 14 C]glycine can account for at least 70% of the total 14 CO 2 produced by the fetus (Thureen et al 1995). Thus, the infused serine in the current study could have been converted to [ 14 C]glycine, which is a possible candidate for oxidation in the fetal liver during IGF-I infusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the late gestation fetal lamb there is no measurable umbilical uptake of serine. All the serine required by the fetus appears to be synthesized within the fetus, largely in the fetal liver from glycine (Cetin et al 1991, Thureen et al 1995). This fetal serine is then taken up in large amounts by the placenta where some is oxidized and some is converted back to glycine and recycled back to the fetus (Marconi et al 1989, Cetin et al 1992.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the ontogeny of the key enzymes of folate metabolism is consistent with a role in the regulation of fetal hepatic serine metabolism (17). In addition, we have shown that fetal ovine hepatocytes are an excellent model in which to study fetal hepatic serine metabolism (11,12,18,19).…”
mentioning
confidence: 88%
“…glycine at approximately 10% enrichment for a further 24 h. Media was harvested at 0 and 24 h, cellular debris was removed by centrifugation, and the media was snap-frozen on dry ice and stored at ĻŖ80Ā°C until analysis. Serine and glycine 13 C media mole percent enrichment and concentration were determined at 0 and 24 h by GC/MS (11,12). Serine and glycine interconversion, production, and utilization rates were determined by stable isotope dilution as we have previously described (11,12).…”
Section: Methodsmentioning
confidence: 99%
“…Others and we have demonstrated that the majority of serine produced by the fetal liver is derived from glycine (2,11,12). However, the regulation of fetal hepatic serine metabolism is unclear.…”
mentioning
confidence: 99%